Al verde si pensa meglio alla GI ! - Salvemini, Mauro (GEOmedia, 2013)
TURAS is a five year Project that will develop visions, feasible strategies, spatial scenarios and guidance tools to help cities address the urgent challenges of: climate change, adaptation and mitigation natural resources shortage, unsustainable urban growth. (http://www.turas-cities.org/ )